Role of Radiographs and Ultrasound in Diagnosing Calcific Tendinitis and Periarthritis in the Wrist and Hand with Ultrasound-Guided Barbotage as Management Tool - Ahuja, Ankita; Lawande, Malini; Daftary, Aditya R. (Indian Journal of Radiology and Imaging, 2021)
Aim To demonstrate the role of radiographs and ultrasound (USG) in the diagnosis of calcific tendinitis and periarthritis in the wrist and hand and the efficacy of USG-guided barbotage for its management.Materials and Methods A retrospective chart review was performed in six patients who presented with acute-onset pain in the wrist and hand varying from 3 days to 2 weeks. Four patients had tenderness over pisiform and two patients had pain along the lateral aspect of the wrist and thumb. Radiographs and USG revealed calcific focus corresponding to the site of pain. USG-guided calcific barbotage and injection was performed for the same and pain relief was assessed immediately and through telephonic follow-up at 6 months using subjective satisfaction score. Data were analyzed using Microsoft Excel 2013.Results Four patients with tenderness over pisiform had flexor carpi ulnaris calcific tendinitis and two patients with pain along the lateral aspect of the wrist and thumb had first metacarpophalangeal calcific periarthritis and abductor pollicis brevis calcific tendinitis on radiographs as well as USG. In post-USG-guided calcific barbotage and injection, all patients had significant immediate and 6 months delayed relief in symptoms with excellent satisfaction scores.Conclusion Acute calcific tendinitis/periarthritis is a benign and self-limiting inflammatory condition. Radiographs are extremely helpful in identifying calcific focus. Ultrasonography in experienced hands is the best modality to identify, confirm the symptomatic calcific focus, and perform USG-guided intervention. USG-guided calcific barbotage is the simplest, quickest, and effective way to treat this condition and avoid compromised functional capacity.
Keywords: barbotage; calcific; periarthritis; tendinitis; ultrasound